PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS STEAM-ESD UNTUK MELATIHKAN KETERAMPILAN PROBLEM SOLVING PESERTA DIDIK PADA MATERI PEMISAHAN CAMPURAN - Yunita Firdaus, Norma; Rosdiana, Laily (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe: (1) students’ problem-solving skills after the implementation of the learning process, (2) the implementation of guided inquiry learning based on STEAM-ESD, and (3) students’ responses toward the implementation of the guided inquiry learning model based on STEAM-ESD. This research employed a quantitative approach using a One Group Pretest-Posttest Design. The subjects of this study were 32 students of class VIII F at SMP Negeri 2 Mojoagung. Data were collected through tests (pretest and posttest), observation sheets of learning implementation, and student response questionnaires. The data were analyzed by identifying the lowest problem-solving skill indicators of each student, calculating the percentage of students in each indicator, and determining the average score per indicator. The results showed an improvement in students’ problem-solving skills, as indicated by the average pretest score of 26.51 (low category) and the average posttest score of 84.08 (very high category). The implementation of learning in Meetings I, II, and III demonstrated that all stages of learning, including the introduction, core activities, and closing activities, were carried out very well, with a mode score of 4 in each meeting, categorized as very good. In addition, students’ responses toward the implementation of the guided inquiry model based on STEAM-ESD were very positive, with an average percentage of 92.08%. These findings indicate that the implementation of the guided inquiry learning model based on STEAM-ESD was effective in improving students’ problem-solving skills, as evidenced by the increase in the average score from the low category in the pretest to the very high category in the posttest, supported by very good learning implementation and highly positive student responses.